Enhancing Supply Chain Resilience through Information Processing and Digital Integration in Managing Risks and Disruptions - Galih , Annindi (Journal Economic Business Innovation, 2024)
Purpose: This study examines the effect of information processing capabilities and digital supply chain integration on supply chain resilience considering the mediating effect of supply chain risk management in the context of the Indonesian manufacturing sector.Method: Study implements Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze data from professionals in the manufacturing industry in Indonesia with respect to the relations between digital tools, risk management, and resilience.Findings: In latest study, the authors highlight how incorporating digital technology and managing for information are two key factors contributing to resilient supply chains, especially during periods of disruption. It highlights that companies using advanced technologies including real-time data analytics and cloud computing are in a better position to identify and manage risks, and therefore recover more quickly when disruptions occur.Novelty: These findings shed new light on the relationship between digital supply chain integration, information processing, resilience, and risk management in an emerging economy such as Indonesia. It builds on existing theories by exploring this dynamic within an industrial setting which has received less attention in the literature.Implications: The findings have important implications for practice in the field of manufacturing in Indonesia, indicating that the production companies need to invest in digital bases and a solid risk management system. These insights can help policymakers and industry leaders design robust and adaptive supply chains that can navigate effectively through global disruptions and uncertainties